Kroje, svéráz, secese a Renáta Tyršová: Výstava svérázu v Obecním domě 1915 - Štěpánová, Irena (Lidé města, 2007)
“The revived movement after Svéráz … in the second year of the war was the first bolder manifestation of the Czech national longing,” Renáta Tyršová describes the exhibition of Svéráz. It was special from several points of view. Beginning of the war had aggravated and intensified perception of political, national and, of course, also social and cultural conditions. It was an uncertain period and full of severe deprivation, but also period of hope. Often, ethnography is perceived, in such tense situations, on a symbolic level. In the Czech context (as well as the European one) there were years of experience with ambitious interpretations of folk culture demonstrations. As if the interest in folk crafts followed social climate and escalated at times of crises or on the contrary euphoria. Both extreme situations resulted in a seemingly similar effect, need to publicly accept the legacy of past generations and manifest one’s own Czech national feeling. One of the favorite, even traditional forms of such demonstrations, was wearing of “national folk costumes”, or rather costumes that could be considered, in urban environment, national folk costumes. To put it differently, they were more less reasonably stylized clothes, inspired by folk costumes. It is natural that public’s attention, since the beginning of the war, returned again to roots and that, at times of generally forced cultural stagnation, the exhibition of costumes rooted in folk tradition, had a predetermined and guaranteed following and success. So much the more that it was an exhibition for women who had to shoulder the weight of unaccustomed responsibility to support the war effort. This event, although limited to Prague and its immediate vicinity, was thus a deed not just professional, artistic and cultural, but also political and to certain extent also emancipating. Its organizers and authors were predominantly women.